PENGARUH PRODUKSI PERTANIAN / PERKEBUNAN TERHADAP PERTUMBUHAN EKONOMI MASYARAKAT DI DESA TOTALLANG KECAMATAN LASUSUA KABUPATEN KOLAKA UTARA - Annisa Annisa; Muh Iqbal; Moch Abd Azis (IAI Al-Mawaddah Warrahmah Kolaka, 2020)
The agricultural sector is a sector that is able to survive in any condition, including when the economic crisis hit various regions. The agricultural sector plays an important role in the economic recovery of the community. The agricultural sector is also one of the main components in the government's programs and strategies for poverty alleviation. Totallang Village is located in a mountainous area with the scope of the village community, most of whom have livelihoods as farmers / gardeners. Workers who work in the agricultural / plantation sector earn income that is used to meet the needs of life and improve household welfare. The formulation of the problem in the research is whether there is an effect of agricultural / plantation production on the economic growth of the community in Totallang Village, Kolaka Utara Regency. The purpose of this study was to determine the effect of agricultural / plantation production on the economic growth of the community in Totallang Village, Kolaka Regency. The research method used in this research is descriptive quantitative research on the effect of agricultural / plantation production on the economic growth of the community in Totallang Village, North Kolaka Regency. Sources of data come from 1) Documentation, 2) Questionnaires, and 3) Observations. The research instrument used was to distribute questionnaires to the people of Totallang Village, Lasusua District, North Kolaka Regency, along with documentation in the form of questionnaire results sheets and documentation photos. The data analysis technique used is the Correlation Test (T Test).Based on the research results from quantitative calculations using the product moment correlation test, the value of t count = 41.477 and the value of t table = 2,000 (t count> t table) then reject Ho and accept Ha, which means there is a significant relationship.